Exploring the intrinsic and extrinsic factors on career choice and development among music graduates in Fujian Normal University, China / Wang Xiaolu - Wang , Xiaolu (2025)
The issues of career among young graduates were frequently raised, particularly with regard to bridging the gap between employment and academics. Music graduates face various challenges in society to retain their professional music skills and to develop their careers. Many studies have examined music students’ or music teachers’ career choice, but the studies on career choice and development among music graduates are limited. The study investigated the music educational experiences, intrinsic and extrinsic factors influencing career choice and career development among music graduates in Fujian, China. An exploratory design was used in which the in-depth interviews was first conducted, followed by the questionnaire survey. The selected participants (N=18 in qualitative study; N=221 in quantitative study) were music graduates with two to twenty years working experience from Fujian, China. The study revealed that career choice was intrinsically motivated by interest, confidence on music skills, commitment to music profession, and extrinsically influenced from work environment and interpersonal impact. Personal self-actualization and interpersonal impact were found to be more significant to career development. The results also indicated the different music educational experiences such as music learning years, types of music major, and instrument type have different effect on factors influencing music graduates’ career choice and development. The findings offered for music students in choosing jobs and help music graduates to bridge the gap between their majors and future careers.